A study on radio ads and its relationship to purchase car among urban commuters / Mohd Izzdihar M. H. Subari - M. H. Subari, Mohd Izzdihar (2013)
This study aims to analyze a study on radio ads and its relationship to purchase car among urban commuters. The impact of radio advertisement towards urban commuter's intention to purchase car are based on descriptive research. This research is basically extending Rajagopal's research paper "Impact of radio advertisements on buying behavior of urban commuters", since he only done on general but not on specific product. Therefore the researcher extending the research on intention to purchase car. The study reveals that the intention to purchase car among urban commuters in response to radio advertisement is highly influenced by the information, economy, communication and cognitive variables. Radio advertisements have quick response on consumer intention to purchase car when they listen to the ads especially when the advertisement are more entertaining while disseminating the message. This study on radio ads and its relationship to purchase car among urban commuters revealed that radio advertisement is highly influenced by the information, economy, communication and cognitive variables that makes the intention of commuters to listen and make a decision to purchase car. A large number of people listen to radio while commuting in urban areas and respond to the broadcast of various commercial messages about cars. There are limited studies available on radio advertisements and the strategy to boost up the listeners to listen radio ads.